Elements of differentiable dynamics and bifurcation theory - Ruelle, David (Academic Press, 1989)
This book provides a rigorous introduction to differentiable dynamics--the mathematical theory underlying chaos and strange attractors. These and related concepts have come to play a key role in physics with the theory of hydrodynamic turbulence, in the natural sciences of meteorology and ecology, and in economics. The basic concepts of differentiable dynamics are presented as they apply to natural phenomena, emphasizing infinite dimensional systems, non-invertible maps, attractors, and bifurcation theory. The book also includes a series of detailed problems as well as appendices that provide both general references and advanced information.